QUADRATIC AND CUBIC NON-LINEARITIES IN A QUASI-LINEAR PARAMETRICALLY-EXCITED SYSTEM - Dinh, Nguyen Van (Vietnam Journal of Mechanics, 1993)
A quasi-linear oscillating system always contains weak factors (negative and positive frictions, exciting forces in resonances, non-linarites of restoring forces) usually characterized by a small parameters €. Recently, some articles have   distinguished the degree of smallness of different factors and interesting phenomena have been found [3, 4]. In the present paper, using the same manner, we shall consider a quasi-linear parametrically-excited system and the difference between the quadratic non-linearity and the cubic one, will be observed.